The creation and dissemination of downloadable information on dementia and driving from a social health perspective. Issue 4 (4th April 2017) - Arai, Yumiko; Arai, Asuna; Mizuno, Yoko; Kamimura, Naoto; Ikeda, Manabu
Abstract : Background: Driving cessation is a likely consequence of progressive dementia. Patients and families can benefit from support through this transition, both to safeguard the patient and public and to help preserve healthy social activity of the patient. Methods: To provide appropriate supportive information, we developed a 35‐page manual ('Supporting family caregivers of older drivers with dementia') available as a free download from our department website. We then informed municipal governments of its availability, tracked website access metrics, and followed up 7 months later with a postal survey to the heads of each municipal government's department of welfare for older citizens. Results: From February to September 2010, the manual was accessed 33 494 times. Of the 1750 municipalities sent surveys, we received 1067 responses (61%). The responses showed that 943 professionals (94.6%) were able to obtain information they needed from the manual, 247 (23%) had used the manual to help residents during the 7 months, and 89% of those who used the manual used it to provide relevant advice to family caregivers. The responses also showed that significantly more use occurred in towns and villages as opposed to cities, consistent with the limited public transportation options in smaller municipalities ( P = 0.002). Conclusions: We anticipate that use of this manual will raise general awareness of this social health issue and facilitate collaborations to provide more social support for those with dementia and their family members.